1999
DOI: 10.3354/meps177115
|View full text |Cite
|
Sign up to set email alerts
|

Diet, provisioning and productivity responses of marine predators to differences in availability of Antarctic krill

Abstract: Knowledge of relationships between prey availability and predator performance is the key to using predators as indicators of the state of marine systems and to assessing potential consequences of competition between natural predators and man for common resources. Fluctuations in the abundance of Antarctic knll are beiieved to have a substantial influence on the reproductive performance of krill-dependent top predator species in the Southern Ocean; few quantifications of such interactions exist. At South Georgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
217
2
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(236 citation statements)
references
References 26 publications
9
217
2
2
Order By: Relevance
“…Local krill ¶ One study of fish meals made from by-products of the Alaska fishing industry revealed no detectable levels of PCBs or other contaminants (58). depletion caused by fishing could also significantly reduce the food resources of other predators, such as seals and whales (70). Unfortunately, existing data on krill abundance and population variables are not sufficient to establish precautionary management of the krill fishery and its effect on the Antarctic ecosystem.…”
Section: Alternatives To Forage Fishmentioning
confidence: 99%
“…Local krill ¶ One study of fish meals made from by-products of the Alaska fishing industry revealed no detectable levels of PCBs or other contaminants (58). depletion caused by fishing could also significantly reduce the food resources of other predators, such as seals and whales (70). Unfortunately, existing data on krill abundance and population variables are not sufficient to establish precautionary management of the krill fishery and its effect on the Antarctic ecosystem.…”
Section: Alternatives To Forage Fishmentioning
confidence: 99%
“…A ntarctic krill Euphausia superba, a key species in Southern Ocean food webs 1 , plays a central role in ecosystem processes and community dynamics of apex predators, and is the target of a commercial fishery 2 . Krill spawn in late spring and their larvae develop during summer, autumn and under the ice in winter to emerge as juveniles in the following spring.…”
mentioning
confidence: 99%
“…1(a)], experiences dramatic interannual variability in its ecosystem. This variability is connected to fluctuations in the local abundance of Antarctic krill (Euphausia superba), the main food source of the higher predators that breed on South Georgia (Croxall et al, 1988(Croxall et al, , 1999Boyd et al, 1994). The krill population at South Georgia is believed not to be self-sustaining (Everson, 1984) but to be maintained instead by oceanic transport of krill from recognised breeding grounds upstream of South Georgia in the vicinity of the Antarctic Peninsula, the South Orkney Islands and the Weddell Sea (e.g.…”
Section: Introductionmentioning
confidence: 99%